The influence of mobile phone use on students’ academic behavior in higher education - Chan Yuen Fook; Suthagar Narasuman (Institute of Advanced Engineering and Science, 2022)
Smartphones have become an inextricable element of life in the twenty-first century. Since there is little research on the relationship between mobile phone use and academic behavior among students in local universities, hence, the current study sought to study the relationship between these two variables in the context of Malaysian higher education. The data from 435 students who answered an online Google Form of survey sent through a WhatsApp link was collected and analyzed using a descriptive correlational research approach. The results indicated that male students displayed a higher level of mobile phone use than female students in higher education. The study also found that negative phone use had a negative relationship with academic behavior, and positive phone use contributed to positive academic behavior. Regression analysis confirmed that excessive mobile phone use and mobile addiction had a higher impact on academic behavior, however, proper mobile use has a positive impact on academic behavior among the students in higher education. The study implies that all the universities need to have better guidelines to regulate the use of mobile phone in the classroom. Overall, the findings are useful in facilitating the monitoring of the proper use of mobile phone for enhancement of learning in tertiary institutions.